Enhanced lipid production in Tetraselmis sp. by two stage process optimization using simulated dairy wastewater as feedstock - Swain, Prajukta; Tiwari, Archana; Pandey, Anjana (Biomass & bioenergy, 2020)
Biofuel production particularly biodiesel has been a subject of investigation worldwide in order to envisage an ecofriendly, renewable source of fuel. Microalgae are one of the key organisms to be utilized in biodiesel production. In the present study, Tetraselmis sp., marine microalgae was investigated for its biodiesel production using the two-stage process optimization method. The first stage consisted of nutrient supplementation with optimization of media (dilution of F/2 media with simulated dairy wastewater) while in second stage, stress factors (nutrient starvation, salinity, pH) were employed with the optimization of factors using response surface methodology. Tetraselmis sp. was grown on different percentage of dairy wastewater and 75% dilution served as better media for growth. The experimental results highlighted that the interaction of nutrient starvation along with salinity was important (p < 0.05). Lipid content was 51.65% in validation experiment and the COD removal was 95% and the major fatty acids were C-16:0, C-18:0, C-18:1.Tetraselmis sp. can be a promising organism for the production of biodiesel coupled with bioremediation of dairy wastewater. •Tetraselmis sp. is a promising microalga for wastewater remediation and biodiesel production.•The two-stage optimization is efficient using Response Surface Methodology.•95% COD removal was achieved in dairy wastewater.•Lipid productivity was 51.65% in the major fatty acids were C-16:0, C-18:0, C-18:1.